Efektivitas Hipnoterapi untuk Menurunkan Depresi pada Mahasiswa Teknik Semester Akhir - Ekka Nurcahyaningrum; Moordiningsih (Nur Science Institute, 2021)
The thesis is a student's final project that should complete so that it can be declared graduated from education. Students must have the ability to assume intellectual responsibility in completing the thesis. It is as part of the academic should be finished by students. For students, the completion of the thesis is often considered a heavy task and burden. Assignment responsibilities affect the condition of students, causing depression, and even ending in death. The study aimed to determine the effect of Hypno-therapy in reducing depression in students of the Faculty of Engineering in Yogyakarta who are preparing a thesis. The subjects in this study were seven engineering students who had moderate depression category. The method used is an experiment with a one-group pretest-posttest design. The research instrument used the BDI II depression scale (Beck Depression Inventory). The analysis using t-test (t-test) with Paired Sample T-test had used to determine the difference in scores before and after the intervention whose have equipped with descriptive analysis. If a significance value of 0.000 (p < 0.05), it means there is a different level of depression between the scores of subjects before and after being given Hypno-therapy. Based on the explanation above, it had could be concluded that Hypno-therapy could reduce depression in engineering students who are writing a thesis.